Efficacy and cost-effectiveness of nutritional intervention in elderly after hip fracture: design of a randomized controlled trial - Verburg Aart D; Severens Johan L; Guldemond Nick A; van Helden Svenjhalmar; Reijven Petronella LM; Breedveld-Peters José JL; Wyers Caroline E; Meesters Berry; van Rhijn Lodewijk W; Dagnelie Pieter C (BMC, 2010)
Abstract Background Hip fracture patients often have an impaired nutritional status at the time of fracture, which can result in a higher complication rate, prolonged rehabilitation time and increased mortality. A study was designed to evaluate the effect of nutritional intervention on nutritional status, functional status, total length of stay, postoperative complications and cost-effectiveness. Methods Open-labelled, multi-centre, randomized controlled trial in hip fracture patients aged 55 years and above. The intervention group receives dietetic counselling (by regular home visits and telephone calls) and oral nutritional supplementation for three months after surgery. The control group receives usual dietetic care as provided by the hospital. Outcome assessment is performed at three and six months after hip fracture. Discussion Patient recruitment has started in July 2007 and has ended in December 2009. First results are expected in 2011. Trial registration ClinicalTrials.gov NCT00523575